Boron Doping of SWCNTs as a Way to Enhance the Thermoelectric Properties of Melt-Mixed Polypropylene/SWCNT Composites - Beate Krause; Viktor Bezugly; Vyacheslav Khavrus; Liu Ye; Gianaurelio Cuniberti; Petra Pötschke (Energies, 2020)
Composites based on the matrix polymer polypropylene (PP) filled with single-walled carbon nanotubes (SWCNTs) and boron-doped SWCNTs (B-SWCNTs) were prepared by melt-mixing to analyze the influence of boron doping of SWCNTs on the thermoelectric properties of these nanocomposites. It was found that besides a significantly higher Seebeck coefficient of B-SWCNT films and powder packages, the values for B-SWCNT incorporated in PP were higher than those for SWCNTs. Due to the higher electrical conductivity and the higher Seebeck coefficients of B-SWCNTs, the power factor (PF) and the figure of merit (ZT) were also higher for the PP/B-SWCNT composites. The highest value achieved in this study was a Seebeck coefficient of 59.7 µV/K for PP with 0.5 wt% B-SWCNT compared to 47.9 µV/K for SWCNTs at the same filling level. The highest PF was 0.78 µW/(m·K2) for PP with 7.5 wt% B-SWCNT. SWCNT macro- and microdispersions were found to be similar in both composite types, as was the very low electrical percolation threshold between 0.075 and 0.1 wt% SWCNT. At loadings between 0.5 and 2.0 wt%, B-SWCNT-based composites have one order of magnitude higher electrical conductivity than those based on SWCNT. The crystallization behavior of PP is more strongly influenced by B-SWCNTs since their composites have higher crystallization temperatures than composites with SWCNTs at a comparable degree of crystallinity. Boron doping of SWCNTs is therefore a suitable way to improve the electrical and thermoelectric properties of composites.